2001
DOI: 10.1016/s0736-0266(00)00019-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal expression of nitric oxide synthase isoforms in healing Achilles tendon

Abstract: We investigated the temporal expressions of the three nitric oxide synthase (NOS) isoforms by semi-quantitative polymerase chain reaction (PCR) assays and by immunoblot analysis, following Achilles tendon transection in rats. Four days after injury, there were increases in the steady-state levels of niRNA for all three NOS isoforms, with peaks for the inducible isoform (iNOS) (23-fold increase) at day 4, the endothelial isoform (eNOS) (24-fold increase) at day 7 and the neuronal isoform (bNOS) (seven-fold incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 51 publications
7
41
0
Order By: Relevance
“…11,12 Our previous reports also confirmed that NOS is upregulated during tendon healing and inhibition of NOS resulted in a significant reduction in cross-section area and failure load of healing Achilles tendon constructs. [13][14][15] We have also noted in our recent clinical trials, that application of topical nitric oxide improved early pain with activity, late functional measures, and outcomes of patients with extensor tendinosis, tendinosis of the extensor mechanism in the elbow, the Achilles and the supraspinatus in the shoulder. [16][17][18] Most of the findings, however, are from the studies on cutaneous wound healing.…”
Section: Introductionmentioning
confidence: 82%
“…11,12 Our previous reports also confirmed that NOS is upregulated during tendon healing and inhibition of NOS resulted in a significant reduction in cross-section area and failure load of healing Achilles tendon constructs. [13][14][15] We have also noted in our recent clinical trials, that application of topical nitric oxide improved early pain with activity, late functional measures, and outcomes of patients with extensor tendinosis, tendinosis of the extensor mechanism in the elbow, the Achilles and the supraspinatus in the shoulder. [16][17][18] Most of the findings, however, are from the studies on cutaneous wound healing.…”
Section: Introductionmentioning
confidence: 82%
“…Generally, after Achilles tendon detachment, BPC 157-treated rats show more blood vessels and dilated capillary beds at injury site in the early healing period (day 4). BPC 157 has angiogenic potential, 6,21,22 directly protects endothelium, 22 counteracts endothelin overproduction, 20 and modulates NO synthesis, and NO system function, 14 and is substantially involved in tendon and bone injury and healing [27][28][29] [i.e., BPC 157 opposes both Larginine-NO synthesis overexpression, and NO synthesis inhibitor N G -nitro-L-arginine methylester (L-NAME) harmful effect also seen in tendon and bone injuries].…”
Section: Discussionmentioning
confidence: 99%
“…Several musculoskeletal entities that have been treated include calcific tendinitis of the shoulder, lateral epicondylitis, delayed union and nonunion of fractures, chronic plantar fasciitis, Achilles and patellar tendinopathies, and osteonecrosis of the femoral head [1][2][3][4][5][6][7][8][9] . Basic-science studies increasingly are providing an understanding of the physiologic mechanisms of pain relief (often immediate) and the modification and repair of the target tissue, which usually requires weeks to months to occur [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Extracorporeal shock-wave treatments have been applied to patients with chronic plantar fasciitis who have failed to respond to multiple conservative pharmacologic and therapeutic interventions [29][30][31][32][33][34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%